Penjadwalan Preventive Maintenance untuk Menurunkan Downtime Mesin Auto Front Wheel di Industri Otomotif - Setiawan, Indra; Adhani, Febryan Zidane (Jurnal Optimalisasi, 2024)
Permo (Motor Company) Industry is one of the companies that operates in the automotive industry, especially motorcycles. The production process in Permo Industry requires machines to support its production process. Among all production engines, the auto front wheel is the engine with the highest downtime rate. The high downtime of the auto front wheel engine is due to an engine failure of 12,000 seconds, or 200 minutes. To reduce downtime, the study included a timetable for checking and preventive replacement of components. The aim of the research is to reduce downtime due to damage to engine components so that production runs smoothly. This step of improvement uses Plan, Do, Check, Action. (PDCA). The results of this study can eliminate 100% of the downtime damage to spring pin press bearing components. The study resulted in an average replacement of spring pin press bearing components every 18 days, a standard using spring pin press bearing components (80.621 shoot), and monitoring of spring p pinpress b bearingcomponents 14 days after replacement.